Influência de alterações do sono na qualidade vocal - Rocha, Bruna Rainho [UNIFESP] (2017)
Objectives: To verify the influence of the sleep quality on the voice. Methods: Self-assessment of the vocal quality, sleep pattern and related data, were collected by an on-line or printed survey. The survey was divided in 3 parts: 1. Demographic data and vocal health aspects, 2. Self-assessment of sleep and vocal quality and the influence that sleep has on voice, 3. Sleep and voice self-assessment tools, which included the Epworth Sleepiness Scale - ESS, Pittsburgh Sleep Quality Index - PSQI and Voice Handicap Index reduced version – VHI-10. 862 people were included (493 women; 369 men), with a mean age of 32 years old (maximum age of 79 years and minimum of 18). Results: The perception of the influence that sleep has on voice showed difference (p<0.050) between sleep and voice self-assessment. In other words, if sleep was self-rated as poor, the voice was also self-rated as bad for individuals who perceived the influence of sleep on voice. There is more risk of presenting alteration on the ESS, PSQI and VHI-10 protocols if sleep and vocal self-assessment are worst, what shows the influence that self-assessment has on the results of these specific tools. The influence of sleep on voice impacts only the VHI-10 score: the greater the perception of this influence, the larger the perceived vocal disadvantage. Sex was not a determinant factor on the outcome regarding the self-assessment instruments. A total of 73 individuals (8.5%) presented deviations for all protocols: ESS, PSQI and VHI-10, while 134 subjects (15.5%) had no deviation for anyone of them. No relationship was found for presence of snoring and vocal quality. The aspects that influence a vocal disadvantage are: voice self-assessment, ESS total score and self-assessment of the influence that sleep has on voice. The absence of daytime sleepiness is a protective factor (OR>1) against vocal disadvantage, meanwhile the presence of daytime somnolence is a damaging factor (OR<1). Conclusion: The sleep quality influences the vocal quality. A bad sleep quality is related to a bad vocal quality. Individuals with vocal disadvantages perceive a greater influence of sleep on voice; the variables that influence these vocal disadvantages are vocal self-assessment, ESS total score, and self-assessment that sleep has on voice. Individuals with daytime somnolence are more likely to have a vocal disadvantage.